Identifikasi Perubahan Luasan Lahan di Wilayah Sub-DAS Cikeruh Menggunakan Citra Landsat 8 dengan Google Earth Engine (GEE): Identification of Changes in Land Area in the Cikeruh Sub-DAS Area Using Landsat 8 Imagery with Google Earth Engine (GEE) - Aditya Rahman Lapian; Edy Suryadi; Kharistya Amaru (Media Ilmiah Teknik Lingkungan (MITL), 2023)
Land cover information is the data neede in the management of watersheds. Identification to obtain land cover using a cloud-based spatial data processing platform Google Earth Engine (GEE). This study aims to identify changes in land area in the Cikeruh sub-watershed area by classifying them using a machine learning basis on GEE. Utilization of landsat imagery is applied in the operation of the Google Earth Engine (GEE) platform using landsat 8 imagery. The analysis method used is the interpretation of Support Vector Machine (SVM) imagery with the identified years since 2015 until 2020. This research still has deficiencies, especially in the validation of land cover classes and area mapped and analyzed.